Physical Fitness Level Of Students Of Kassi-Kassi Elementary School, Makassar City - Hanafi, Surya (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
The type of research in this study is quantitative descriptive. This study is a collection of data that will later be poured into a report and description to determine the level of physical fitness of students of SD Inpres Kassi-Kassi, Makassar City. The method used is a descriptive method, normality test and categorization. The population in this study was 88 students and the population of male students in grades V-VI of SD Inpres Kassi-Kassi, Makassar City consisted of 30 students. The selection/determination of the sample, namely female students. This was done intentionally (purposive) with the consideration that the average level of physical fitness was almost the same. The sample to be studied using the purposive random sampling technique (random) by lottery so that the number of samples was 60 students of SD Inpres Kassi-Kassi, Makassar City. The techniques used in this study were interview techniques, observation, tests and documentation. The research results obtained were from 30 students who took the physical fitness test on 5 test items of elementary school students in Kassi-Kassi, Makassar City, as many as 18 students were in the "Moderate" category or 65%, 12 students were in the "Less" category or 40%. Based on the research results obtained and referring to each discussion, it can be concluded that the level of physical fitness of students in SD Inpres Kassi-Kassi, Makassar City is in the moderate classification